Analyzing Social and Psychological Impacts: Shifting Student Interaction from Teachers to ChatGPT in the Learning Process - Kharis, Selly Anastassia Amellia; Indriyani, Annisa (Universitas Pahlawan Tuanku Tambusai, 2024)
The integration of artificial intelligence (AI), specifically ChatGPT, into education it may reduce social engagement among students and teachers also can diminish critical thinking skills, as students might prefer easy answers over deep, analytical thinking. This study investigates the social and psychological impacts of shifting student interactions from teachers to AI. The research method used is a literature study by reviewing seceral relevant and current literature. The result of this study is the reduction in face-to-face interaction can hinder the development of essential communication and collaborative skills between students and teachers as an impact of the intensity of AI use. Moreover, the dependency on AI could lead to a superficial understanding of subjects, with students accepting information at face value without thorough evaluation, thereby affecting their overall academic development and comprehension. Additionally, the study underscores the necessity of developing emotional intelligence, which AI cannot effectively nurture. The findings underscore the irreplaceable role of educators in nurturing cognitive and socio-emotional development, advocating for a balanced approach to integrating AI in education